APPLICATION OF GUIDED INQUIRY METHOD IN LEARNING LANGUAGE FOR UNDERGRADUATE NURSING STUDENTS - Moh. Zainudin; Nurjanah, Eka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses in detail the planning, implementation, and evaluation of the application of the guided inquiry method for undergraduate nursing students at the Universitas Bina Sehat PPNI Mojokerto. The lecturer solely serves as a facilitator through the guided inquiry method, which enables students to actively participate in learning activities. Learning materials for making proposals for community services, implementing community services, and writing articles about community services are the implementation of the guided inquiry method. The research design used is qualitative, which obtains descriptive information through interviews, observations of people's behavior, or written or spoken statements from participants. Observation, interviews, and documentation are data collection. Data analysis is summarized as (1) data compression in this activity, data are chosen based on the level of relevance and the relationship to data groupings. In addition, data are collected into one unit, and codes are created, (2) presenting by assembling related data, and (3) making conclusions to understand the significance of the sporadic symptoms. The use of the guided inquiry method in language acquisition can be divided into three categories based on the findings and discussion; planning, implementing and evaluating the application of the guided inquiry method. The guided inquiry approach is put into the students’ learning experience of the lecturer planning section. Students use the guided inquiry approach in the application, starting with problem-solving, hypothesis-making, evidence-gathering, hypothesis-testing, and conclusion-drawing. Subsequently, the researcher made an evaluation criterion to test students' proficiency through the guided inquiry method. When the guided inquiry approach is used, students get learning opportunities, especially ones that help them develop their speaking and writing skills, which are two forms of productive language. The students' capacity to conduct teaching at school and produce articles for community service serves as evidence regarding this.